The history of Akbar - Ebü'l-Fazl el-Allâmî, 1551-1602. (Cambridge, MA Cambridge, MA Cambridge, MA Cambridge, MA Cambridge, MA Cambridge, MA)
6 cilt (1 c. xxix, 614 sayfa ; 2. c. xxviii sayfa, [2] sayfa harita, 560 sayfa ; 3. c. xxviii sayfa, [2] sayfa harita, 656 sayfa ; 4. c. xxviii sayfa, [2] sayfa harita, 622 sayfa ; 5. c. xxviii sayfa, [2] sayfa harita, 745 sayfa ; 6. c. xxviii sayfa, [2] sayfa harita, 647 sayfa)